How to Outsmart Investment Scam? (Comparing Legitimate vs Scam Investment using Business Model Canvas and Value Proposition Design) - Irawan, Andi (IJTB (International Journal of Technology And Business), 2019)
investment is one way to increase the value of one's wealth. Investment can be divided into real and financial sector. Many people with minimum to no financial literacy become victim of investment scam with many form. This paper purpose is to exercise simple and applicable tool and criteria to quickly distinguish legitimate vs  investment scam by comparing their business model canvas and and value proposition design. Data was taken from in depth interview with investment scam victim. From business model canvas comparison, this paper showed that that investment scam generally do not have permission from the Financial Services Authority and other relevant authorities, the business model is too good to be true (unclear), no or too simple website, no official office, no investment manager. While from value proposition design comparison, it is found that investment scam offers very high return way above industry normal return, offer zero risk, targeting medium to high income people (including retiree) who have minimal or no investment knowledge. As solution initiative, this paper offer comprehensive approach in five aspects: policy, regulation, education and socialization, and information-communication technology. Further, FSA may establish mobile application featuring education in financial planning, a list of authorized investment companies, and industry normal return of investment are necessary to prevent the next victim.